1993
DOI: 10.3102/00028312030001095
|View full text |Cite
|
Sign up to set email alerts
|

Access to Print for Children of Poverty: Differential Effects of Adult Mediation and Literacy-Enriched Play Settings on Environmental and Functional Print Tasks

Abstract: This study examined the effects of adult mediation and literacy-enriched play settings on environmental and functional print tasks for 177 minority preschoolers reared in poverty. Eight Head Start classrooms were assigned to one of three conditions: (a) a literacy-enriched generic ' 'office'' play setting with an adult (referred to as "parent-teacher") encouraged to actively assist children in learning about literacy; (b) a literacy-enriched off ice play setting with a parent-teacher asked to monitor the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(66 citation statements)
references
References 28 publications
(26 reference statements)
4
62
0
Order By: Relevance
“…Research has found that teachers must draw children's attention to print because, even when presented in interesting illustrations, children do not look at the text without adult mediation (Evans & Saint-Aubin, 2005). Further work has shown that children's ability to read and use environmental print increases, when adults facilitate children's exposure to such print (Neuman & Roskos, 1993;Vukelich, 1994). In addition, in a series of studies, Justice and colleagues have demonstrated the benefits of print referencing (i.e., drawing attention to letters, words, and other print) during storybook reading on children's literacy skill development (Justice, Kaderavek, Fan, Softa, & Hunt, 2009;McGinty, Breit-Smith, Fan, Justice, & Kaderavek, 2011).…”
Section: Writing Environmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Research has found that teachers must draw children's attention to print because, even when presented in interesting illustrations, children do not look at the text without adult mediation (Evans & Saint-Aubin, 2005). Further work has shown that children's ability to read and use environmental print increases, when adults facilitate children's exposure to such print (Neuman & Roskos, 1993;Vukelich, 1994). In addition, in a series of studies, Justice and colleagues have demonstrated the benefits of print referencing (i.e., drawing attention to letters, words, and other print) during storybook reading on children's literacy skill development (Justice, Kaderavek, Fan, Softa, & Hunt, 2009;McGinty, Breit-Smith, Fan, Justice, & Kaderavek, 2011).…”
Section: Writing Environmentmentioning
confidence: 94%
“…Although environmental print by itself may not significantly improve children's early literacy or writing skills, studies suggest that pairing environmental supports with teacher modeling or support does. For example, Neuman and Roskos (1993) found that redesigning Head Start classrooms to incorporate more literacy related play (e.g., office or post office dramatic play and additional opportunities to interact with print) and encouraging parent volunteers and teachers to increase children's involvement in these literacythemed centers was significantly related to children's ability to read environmental print and label functional print items. In their study, children who were exposed to print rich literacy environments and had adults facilitate their interactions with such materials were able to read environmental print better than children who were simply exposed to the materials.…”
Section: Environmental Supports For Early Writingmentioning
confidence: 97%
“…Researches indicated that when disadvantaged parents were provided with access to resources and information, they contributed significantly to their young children's language and literacy development (Jordan, Snow, & Porche, 2000;Neuman & Gallagher, 1994;Neuman & Roskos, 1993). A better promotion of children's books and a better organization of children's libraries might give LSES parents and their children many opportunities to engage with children's books.…”
Section: Resultsmentioning
confidence: 99%
“…In a 1998 study, multi-age enriched play settings were shown to provide more opportunities for interactions around literacy content (Christie & Stone, 1998). Other studies have indicated that shared enactment of stories increases children's engagement in play (Fein, Ardilla-Rey, & Groth, 2000), language strategies in play support other literacy strategies (Branscombe & Taylor, 2000), and combining a literacy-rich play context with active adult mediation improves children's ability to read environmental print (Neuman & Roskos, 1992;1993). There is much other supporting literature on topics ranging from teacher involvement in sociodramatic play, to the relationship of play and culture.…”
Section: Benefits Of Play For All Agesmentioning
confidence: 99%